Hydrostatics Curve Approach as a Design Development of Fishing Canoe With Bilge Keel to Improve Rolling Period - Bima Ramadhani; Yeddid Yonatan Eka Darma; I.G.N.A. Satria Prasetya; Mohammad Danil Arifin (Institut Teknologi Sepuluh Nopember, 2023)
Canoes are currently starting to be in demand among the public, some of the activities that can be carried out using canoes include fishing, traveling or water sports. Canoes are still in great demand compared to other types of boats, because canoes are very stable in calm water. Its stability is the reason why this type of boat is usually chosen as the type of boat for beginners and family outings. Unfortunately the canoe is less stable in challenging waters. When the weather or waters are calm the canoe is reliable, however when it turns bad with very choppy water and high winds a skilled oarsman is needed to keep the boat afloat. The downside with canoes is having good primary stability but usually poor secondary stability. This means the boat is only stable in still water. If the wind blows hard and creates very choppy water, then the canoe or canoe will lose stability and rolling motion which can cause accidents for its users. Therefore I will try to use a flat bottom canoe design by adding a bilge keel to the hull of the canoe in hopes of adding stability. I tried to compare the stability and roll period of a regular canoe with one that used 1 pair of bilge keels, 6.25 cm wide, 0.8 cm thick and 30 degrees angled. Variations in the length of the bilge keel used include 0.875, 1.05 and 1.225 m. Mounted in the middle of the ship, not too forward or backwards.